Subclinical Left Ventricular Systolic Dysfunction in Hospitalized Patients with COVID-19 by Strain: A 30-Day Echocardiographic Follow-Up - Pedro Morillas-Blasco; Paula Guedes-Ramallo; Nuria Vicente-Ibarra; Marina Martínez-Moreno; Andrea Romero-Valero; Antonio García-Honrubia; Elena Castilla-Cabanes; José Antonio Viedma-Contreras; Mar Masiá-Canuto; Jesús Castillo-Castillo; Sandra Santos-Martínez (Medicina, 2023)
Background and Objectives: Available studies confirm myocardial injury and its association with mortality in patients with COVID-19, but few data have been reported from echocardiographic studies. The aim of this study was to identify subclinical left ventricular dysfunction by global longitudinal strain (GLS) and its evolution in the short term in hospitalized patients with COVID-19. Materials and Methods: Thirty-one consecutive noncritical patients admitted for COVID-19 were included. Information on demographics, laboratory results, comorbidities, and medications was collected. Transthoracic echocardiograms were performed using a Philips Affinity 50, at the acute stage and at a 30-day follow-up. Automated left ventricular GLS was measured using a Philips Qlab 13.0. A GLS of <–15.9% was defined as abnormal. Results: The mean age was 65 ± 15.2 years, and 61.3% of patients were male. Nine patients (29%) had elevated levels of high-sensitivity troponin I. Left ventricular ejection fraction was preserved in all; however, 11 of them (35.5%) showed reduced GLS. These patients had higher troponin levels (median, 23.7 vs. 3.2 ng/L; p < 0.05) and NT-proBNP (median, 753 vs. 81 pg/mL; p < 0.05). The multivariate analysis revealed that myocardial injury, defined as increased troponin, was significantly associated with GLS values (coefficient B; p < 0.05). Follow-up at 30 days showed an improvement in GLS values in patients with subclinical left ventricular dysfunction (−16.4 ± 2.07% vs. −13.2 ± 2.40%; p < 0.01), without changes in the normal GLS group. Conclusions: Subclinical left ventricular dysfunction is common in noncritical hospitalized patients with COVID-19 (one in every three patients), even with preserved left ventricular ejection fraction. This impairment tends to be reversible on clinical recovery.